MEASURING THE ECONOMIC LEVEL OF TRADITIONAL ISLAMIC BOARDING SCHOOLS IN MAGELANG - Kartika; Shanaya; Septi Ikhwan; Farra Ikhwan; Imel (Transpublika Publisher, 2023)
Traditional Islamic boarding schools are the oldest educational institutions in Indonesia, where students learn many important materials regarding Islamic studies such as: Tauhid, Fiqh, and Tasawwuf. Islamic boarding schools must be able to organize and manage their institutions properly as an effort to maintain Islamic boarding schools and the daily needs of the students. The economy of traditional Islamic boarding schools is certainly different from modern Islamic boarding schools which receive regular income. This research aims to find out the economic and educational systems contained in traditional Islamic boarding schools, to find out the various activities carried out in traditional Islamic boarding schools and what things are needed by students of traditional Islamic boarding schools. This study uses a descriptive statistical approach with a survey method. The number of samples used was 10 from the board of the Islamic boarding school. The results of this study indicate that the mean and median values are the same, meaning that these values are still stagnant and have not changed. With the economic limitations that exist in the Islamic boarding school, it is necessary to develop and empower the economy for the students there.